Resistance and Colonialism
XVII, 347 p. 5 illus.
Keywords: ‘This splendid collection leaps well ahead of cruder, binary understandings of resistance in the colonial context. By dint of its attention to oral, archival, and local sources it understands that resistance is always multi-faceted, complex, and multi-purposed; that the metropolitan conceit that all the colonized can possibly think about is their colonizer, is wishful thinking. Do read this collection for its geographical breadth, its historical depth, and its sophistication.’ —James C. Scott, Sterling Professor of Political Science and Anthropology, Yale University, USA This volume offers a critical re-examination of colonial and anti-colonial resistance imageries and practices in imperial history. It offers a fresh critique of both pejorative and celebratory readings of ‘insurgent peoples’, and it seeks to revitalize the study of ‘resistance’ as an analytical field in the comparative history of Western colonialisms. Itexplores how to read and (de)code these issues in archival documents – and how to conjugate documental approaches with oral history, indigenous memories, and international histories of empire. The topics explored include runaway slaves and slave rebellions, mutiny and banditry, memories and practices of guerrilla and liberation, diplomatic negotiations and cross-border confrontations, theft, collaboration, and even the subversive effects of nature in colonial projects of labor exploitation.